De-Escalation of Broad-Spectrum Antibiotics After Relevant Culture Reports in Medical Ward Patients Audit from A Tertiary Care Hospital in South India: Pharmaceutical Science-Medicine - Sathyamurthy. P, Dr.; Rajkumar. M, Dr. (International Journal of Life Science and Pharma Research, 2022)
Prolonged and improper usage of antibiotics has been shown as a main reason for the emergence of multidrug-resistant pathogens.Antimicrobial stewardship (AMS) programs have been shown to reduce the antibiotics usage and the rate of emergence of resistance. De-escalation of antimicrobials is an important component of AMS. AMS programmes require regular auditing and feedback for proper implementation and continuous improvement. Hence we did this clinical audit with the main aim of estimating the de-escalation rates and identifying the possible reasons for non-de-escalation in our centre. Case sheets of the patients admitted between 1st October 2020 to 31st December 2020 were screened during discharge for data for de-escalation and reasons for non-de-escalation. Cefeprazone-sulbactum (32%) was commonly used empirical monotherapy in the audited period. De-escalation rate after positive culture reposts was 28%. Serious clinical illness (36%) was found to be the most common reason for non-de-escalation. De-escalation was not done in nearly 25% of eligible instances without a proper justification.